As estratégias de gestão da atenção à saúde dos radioacidentados pelo Césio 137 do Estado de Goiás - Sousa, Hildêth Pereira de Oliveira (2023)
With the rupture of a Cesium-137 capsule, in September 1987, Goiânia-Goiás experienced the biggest reported radiological accident in the world. In this study, we wanted to consolidate strategic and legal information on the institutional evolution aimed at monitoring radioactive victims of Cesium-137 in Goiás, over a period of 35 years. OBJECTIVES: To know the strategies for managing the health care of those who have radioactive accidents caused by Cesium-137. METHODOLOGY: Descriptive and bibliographic methods were used to deal with the normative characteristics, being a descriptive-analytical study, with a qualitative and quantitative approach referring to management strategies aimed at monitoring radioactive victims by Cesium-137. To collect data on legislation, public databases were used. Patient data were obtained from SISRAD, generating a database. Data from the SES-GO Health Information Platform (Conecta SUS) were consolidated from the database, as well as information from the SUS Department of Informatics (DATASUS) for georeferencing and demonstration of the location of patients in the state, demonstrating the macro-regions and sanitary health regions in the state of Goiás. RESULTS: It was evident that over the 35 years there was a total edition of 15 basic legal orders, such as laws and decrees. As for patient follow-up of the patients, there was a division into three groups, according to the level of exposure. Thhe State Center for Assistance to Radio-Accidents (CARA) followed the initial standard of care, monitoring Groups I and II, as well as their descendants. The seven cases of cancer that occurred in 6 patients from these groups in the period of 30 years (1987-2017), did not present a statistically different number from the population of Goiânia not exposed until that moment. Group III presents dynamic insertion due to evaluation processes or judicial decision and already follow the same monitoring parameters as the groups that had a higher degree of health impairment directly due to the accident. Monitoring during the COVID-19 pandemic, starting in 2020, followed the standards established by SES-GO. However, until December 2022, 06 deaths were recorded as a result of COVID-19, of which: 01 adult man in group II, and 4 men and 1 woman in group III. FINAL CONSIDERATIONS: CARA is guided by the fulfillment of its role and continues to provide all services through the Unified Health System (SUS), in a direct and regulated manner, following the protocols and schedules established for the proper assistance to victims of radioactive accidents.